Short telomeres drive pessimistic judgement bias in zebrafish - Espigares, F. (Biol Lett, 2021)
The role of telomerase reverse transcriptase has been widely investigated in the contexts of ageing and age-related diseases. Interestingly, decreased telomerase activities (and accelerated telomere shortening) have also been reported in patients with emotion-related disorders, opening the possibility for subjective appraisal of stressful stimuli playing a key role in stress-driven telomere shortening. In fact, patients showing a pessimistic judgement bias have shorter telomeres. However, in humans the evidence for this is correlational and the causal directionality between pessimism and telomere shortening has not been established experimentally yet. We have developed and validated a judgement bias experimental paradigm to measure subjective evaluations of ambiguous stimuli in zebrafish. This behavioural assay allows classification of individuals in an optimistic–pessimistic dimension (i.e. from individuals that consistently evaluate ambiguous stimuli as negative to others that perceive them as positive). Using this behavioural paradigm we found that telomerase-deficient zebrafish (tert(−)(/−)) were more pessimistic in response to ambiguous stimuli than wild-type zebrafish. The fact that individuals with constitutive shorter telomeres have pessimistic behaviours demonstrates for the first time in a vertebrate model a genetic basis of judgement bias.